PERAN KOMUNIKASI BISNIS PADA PT. SRIWIJAYA DISTRIBUSINDO RAYA - Sapta Yuliansyah; Ahmad Rozikin (Nusantara Hasana Journal, 2025)
This research aims to investigate and explain the application of business communication in marketing ice cream products, namely Glico Wings at PT Sriwijaya Distribusindo Raya Palembang. In addition, this research also wants to identify the factors that support and hinder the company in achieving its sales target. In sales, the marketing team has an important role to achieve the desired target. However, in reality, the marketing team faces many heavy workloads as well as a lack of support from stakeholders. One of the challenges faced is the limited promotional programs to partner outlets that can increase the sales spirit of Glico Wings ice cream, especially in the midst of intense competition with other competitors. The method used in this research is descriptive qualitative, with data collection through observation, interviews, and documentation. The results revealed that the marketing team has a strategic role in achieving various company targets that have been set. However, with the lack of adequate support, it will be difficult to compete with existing rivals.